Effect of Molar Concentration on Optical Absorption Spectra of ZnS:Mn Nanoparticles - Ravi Sharma; B. P. Chandra; D. P. Bisen (E-Journal of Chemistry)
The present paper reports the synthesis and characterization of luminescent nanocrystals of manganese doped zinc sulphide. Nanocrystals of zinc sulphide were prepared by chemical precipitation method using the solution of zinc chloride, sodium sulphide, manganese chloride and mercaptoethanol was used as the capping agent. It was found that change in the molar concentration changes the particle size. The particle size of such nanocrystals was measured using XRD pattern and it is found to be in between 3 nm – 5 nm. The blue-shift in absorption spectra was found with reducing size of the nanoparticles